Periodisasi Penulisan Al-Qur'an Masa Klasik Islam - Haikal Al Fiqri (Program Studi Sejarah dan Kebudayaan Islam Sekolah Tinggi Agama Islam Program Studi Sejarah dan Kebudayaan Islam, 2025)
The writing of the Qur'an actually began from the moment the first revelation was received until the final revelation was revealed. During the caliphate of Abu Bakr, verses that were scattered and written on various materials such as animal skins and leaves were collected (a process known as jam'ul Qur'an) and stored in the house of Hafsah. Later, during the reign of Caliph Uthman ibn Affan, Zaid was once again appointed to lead a team tasked with compiling and transcribing the Qur'anic verses from various written sources. This study uses library research with a descriptive-analytical approach. During the Umayyad Dynasty, the writing of the Qur'an developed with the addition of diacritical marks such as dabt, syakl, and nuqath, and began to be written using the Kufic script. Later, during the Abbasid Dynasty, notable calligraphers such as Ibn Muqlah emerged, and the script style shifted to the Naskh script. With the advancement of technology, Harun al-Rashid purchased paper from China and developed printing technology, marked by the establishment of paper factories in Baghdad and Samarkand. From that point on, the Qur'an began to be widely distributed, eventually being printed for the first time in Venice around 1537/1538 by the Fratelli brothers using a printing press invented by Johannes Gutenberg of Germany in 1440. Additionally, the oldest known Qur'anic manuscript in the world was discovered in Birmingham, England.